Propriedades físico-mecânicas de resinas ortodônticas com diferentes fotoiniciadores fotoativadas com LED de amplo espectro - Roseira, Priscila Maito (2017)
The aim of this study was to evaluate the physical and mechanical properties of experimental orthodontic resins containing different photoinitiators, in comparison to a commercial resin, photoactivated directly or through ceramic bracket by a polywave LED. A commercial orthodontic resin (Transbond XT), and three experimental resins, composed by a Bis-GMA matrix containing different photoinitiation systems: 1) phenyl-propanedione (PPD) + DMAEMA amine, 2) bys- acylphosphine oxide (BAPO) or 3) camphorquinone (CQ) + DMAEMA amine) were used. The resins were photoactivated by Valo Ortho light curing unit, in a direct way (control) or through ceramic bracket. The degree of conversion (DC) was determined by Raman spectrophotometry. The inicial Knoop hardness (KHN1) was assessed, and, after 24 hours of storage in 100% ethanol, KHN was assessed again (KHN2) for softening rate evaluation. Data were submitted to two-way ANOVA and Tukey’s test (α= 0,05). Differences were observed among the resins, the DC was higher for the BAPO-containing resin (76,42%- directly way) and lower for the commercial resin Transbond XT (40,80%- directly way). The BAPO resin showed the higher KHN1 values (53,32%- overall average), and the experimental resin PPD showed the worst performance (25,38- overall average). The softening rate was higher to PPD resin (49,19%- overall average), significantly higher than Transbond XT that showed the lower softening rate (40,02%- overall average). The photoactivation condition affected the evaluated properties, being that the best performances were reached when the resins were activated in a direct way. Thus, could be concluded that the photoinitiator type and the photoactivation condition significantly influenced the physical and mechanical properties of the assessed materials, and PPD and BAPO could be considered alternatives to substitute the conventional system CQ/amine.